2017
DOI: 10.1016/j.addbeh.2017.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Daily-level associations between PTSD and cannabis use among young sexual minority women

Abstract: Introduction Sexual minority women have elevated trauma exposure and prevalence of posttraumatic stress disorder (PTSD) compared to heterosexual women and they are also more likely to use cannabis, although no research has examined relationships between PTSD and cannabis use in this population. Daily- level methodologies are necessary to examine proximal associations between PTSD and use. Methods This study included 90 trauma-exposed young adult women who identified as sexual minorities (34.4% identified as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…However, Stults et al [40] found that IPV victimization and perpetration were associated with significantly greater odds of cannabis, stimulant, and other drug use among adolescent SMM. Further, the longer-term sequelae of victimization may predict substance use; adolescent SMW with higher levels of PTSD symptoms reported more frequent cannabis use than adolescent girls with lower-level symptomatology [63]. …”
Section: Resultsmentioning
confidence: 99%
“…However, Stults et al [40] found that IPV victimization and perpetration were associated with significantly greater odds of cannabis, stimulant, and other drug use among adolescent SMM. Further, the longer-term sequelae of victimization may predict substance use; adolescent SMW with higher levels of PTSD symptoms reported more frequent cannabis use than adolescent girls with lower-level symptomatology [63]. …”
Section: Resultsmentioning
confidence: 99%
“…Cannabis use has become increasingly common amongst patients with PTSD [83]. Although there is mixed data regarding the use of cannabis as a treatment for PTSD, current research has shown a strong positive association between PTSD symptom severity and daily cannabis use [43]. There is evidence that supports the notion that individuals with PTSD use cannabis as a means for coping with symptoms, primarily involving insomnia in contrast to anxietyrelated symptoms [10,56].…”
Section: Post-traumatic Stress Disorder (Ptsd)mentioning
confidence: 95%
“…If a range was given (e.g. 5-10 minutes, see [48]) we used the middle value (7.5 minutes in this case). For purposes of administration, we separated devices into personal digital assistants (PDAs), smartphone-owned, smartphone-loaned, internet-based or interactive voice responding.…”
Section: Extraction and Codingmentioning
confidence: 99%